FEATURES AND METHODS OF TEACHING LEGAL ENGLISH: A PRACTICAL APPROACH IN THE AI ERA (American Journal of Interdisciplinary Research and Development, 2024)
Teaching Legal English has become a key aspect of preparing students for global legal practices. This article delves into the distinctive characteristics of Legal English and explores practical teaching strategies, with a focus on keeping the learning process personal in an age where artificial intelligence (AI) tools are increasingly present. By sharing experiences from teaching at a university, the article suggests methods that blend traditional, interactive techniques with new technologies in a balanced way. The aim is to help students master the complexities of Legal English while keeping human interaction central to their learning journey.